Faktor-Faktor Yang Mempengaruhi Penghindaran Pajak Perusahaan Properti Dan Real Estate - Taufianto Ekaputra, Widyasari (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to find whether there is the influence of liquidity , its satisfactory profitability as , and leverage against Tax Avoidance. Secondary data was used in the study with in data collection that is obtained on industrial Property and Real Estate sector who are enrolled in the Indonesia Stock Exchange in the year 2014-2016. Sample was used in the study as many as 26 companies and exclusively on the SPSS 23.0 version as a program data processing. This report is written with the sampling method of purposive technique. Based on research that is done, obtained the results of research is as follows: (1) Liquidity has no significant impact on Tax Avoidance. (2) Profitability has no significant impact on Tax Avoidance .(3) Leverage significant impact on Tax Avoidance